ADOPTION OF INFORMATION TECHNOLOGY AND ACCEPTANCE OF LEARNING MANAGEMENT SYSTEMS DURING PANDEMIC COVID-19 IN INDONESIA - Umi Chotijah; Harunur Rosyid; Fitri Retrialisca; Mochammad Ichsan (Faculty of Computer Science Universitas Indonesia, 2022)
The COVID-19 pandemic that emerged in 2019, in wuhan, Hubei province, China has spread almost throughout the world, including Indonesia. The impact of the virus is that the government has issued public policies, which include social distancing, social isolation, and self-quarantine. Various sectors must implement the policy. Several companies in Indonesia have to enforce working from home for all their employees, including educational institutions in Indonesia, from the level of Playgroups, Early Childhood Education, Kindergartens, Elementary Schools, Junior High Schools, Public High Schools or Senior High Schools. Vocational High Schools and Universities also apply an online learning process from home. Information Technology provides solutions for the education system in Indonesia in these difficult times, so that the learning process can continue. In previous studies, an exploration of the Unified Theory of Acceptance and Use of Technology (UTAUT) model with social isolation variables, and corona fear moderating variables was carried out on the Behavioral Intentions of the Learning Management System and the Behavior of the Use of Learning Management Systems among General or Vocational High School students. Data analysis using Smart Partial Least Square (PLS) and Structural Equation Modeling (SEM). The findings show a positive relationship of Performance Expectations (PE), Effort Expectations (EE), Social Influence (SI), and Social Isolation on LMS Behavioral Intentions and, also between LMS Behavioral Intentions and Use Behavior. In addition, the results of the moderation analysis show that the fear of Corona only moderates the relationship between Performance Expectations and Social Influences with LMS Behavioral Intentions. The findings imply the need to increase the behavioral intentions of LMS users among college students or students.